Decision-making tool for national implementation of the Plant Treaty's multilateral system of access and benefit-sharing - Joint Capacity Building Programme (Bioversity International, 2018)
This decision making tool is designed to assist national policy makers and other stakeholders to identify appropriate measures to implement the Plant Treaty’s multilateral system of access and benefit-sharing in their countries. It is the product of eight years of experience working with partners in numerous countries developing national policies under the overall framework of the FAO/Bioversity International/ITPGRFA Secretariat Joint Capacity Building Programme for Developing Countries on Implementation of the ITPGRFA and its Multilateral System of Access and Benefit-sharing.